THE INFLUENCE OF RETURN ON INVESTMENT, CURRENT RATIO, DEBT TO EQUITY RATIO , EARNING PER SHARE,AND FIRM SIZE TO THE DIVIDEND PAY OUT RATIO IN BANKING INDUSTRIES LISTED AT INDONESIA STOCK EXCHANGE PERIOD 2013-2018 - Tania Rahmadi, Zara (Dinasti International Journal of Digital Business Management, 2020)
This study aimed to examine the factors that influence the ratio of dividend payments in the banking industry. These factors include return on investment, current ratio, debt to equity ratio, earnings per share, and firm size. The technique for sampling using purposive sampling while the sample used in this study was 6 banking companies listed on the Indonesia Stock Exchange in 2014-2018. The analytical method used in this study was a panel data regression model (a combination of time series and cross section). From the results of the study, showed that first, the return on investment did not significantly affect the dividend payout ratio; second, the current ratio did not significantly influence the dividend payout ratio; third, the debt to capital ratio had a significant effect on dividend payout ratios; fourth, earnings per share did not significantly influence to the ratio of dividend payout ratios and the last was that the size of the company had a significant effect on the ratio of dividend payout ratios. From these results it is expected that can be used as a reference, both by company management and by investors in determining investment strategies.